Past and present of the psychological study of language: a behavioral review - Montgomery Urday, William (1999)
It is exposed a general review on what has been the psychological study of the language through the history, departing from the first reflections and hypothesis on its ontogeny and relationships to other disciplines, until arriving to the contemporary directions. Between these are distinguished three principal blocks: a) psycholinguistic, b) constructivism or of the cognitive development, and c) behaviourist. After discussing critically the traditional ideas exposed by the representative of such current (as well as their divergences) to the light of their state and current followers, is made a short exploration taking into account the coincidence points that there are between these last. It is concluded that the future address, in terms of empirical practice, it has an interactive behavioural trend with communicational implications.